Surgical Repair of Distal Biceps Femoris Avulsion Injuries in Professional Athletes. Issue 3 (19th March 2021) - Thompson, Joshua W.; Plastow, Ricci; Kayani, Babar; Moriarty, Peter; Asokan, Ajay; Haddad, Fares S.
Background: Understanding the optimal management of distal biceps femoris avulsion injuries is critical for restoring preinjury function, restoring hamstring muscle strength, increasing range of motion, and minimizing risk of complications and recurrence. Due to the rarity of these injuries, prognosis and outcomes within the literature are limited to case reports and small case series. Purpose: To assess the effect of surgical repair for acute distal avulsion injuries of the biceps femoris tendon on (1) return to preinjury level of sporting function and (2) time to return to preinjury level of sporting function, patient satisfaction, and complications. Study Design: Case series; Level of evidence, 4. Methods: This prospective single-surgeon study included 22 elite athletes (18 men [82%], 4 women [18%]; mean age, 26 years; age range, 17-35 years; mean body mass index, 25.3 ± 4.1 kg/m 2 ) undergoing primary suture anchor repair of avulsion injuries of the distal biceps femoris confirmed on preoperative magnetic resonance imaging. Predefined outcomes relating to time for return to sporting activity, patient satisfaction, complications, and injury recurrence were recorded at regular intervals after surgery. Minimum follow-up time was 12 months (range, 12.0-26.0 months) from the date of surgery. Results: The mean time from injury to surgical intervention was 12 days (range, 2-28 days). All study patients returned to their preinjury level of sporting activity, predominately professional soccer or rugby. Mean time from surgical intervention to return to full sporting activity was 16.7 ± 8.7 weeks. At 1- and 2-year follow-up, all study patients were still participating at their preinjury level of sporting activity. There was no incidence of primary injury recurrence, and no patients required further operation to the biceps origin. Conclusion: Surgical repair of acute avulsion injuries of the distal biceps femoris facilitated early return to preinjury level of function with low risk of recurrence, low complication rate, and high patient satisfaction in elite athletes. Suture anchor repair of these injuries should be considered a reliable treatment option in athletes with high functional demands to permit an early return to sport with restoration of hamstring strength.